Development of Inclusion Complexes With Relative Humidity Responsive Capacity as Novel Antifungal Agents for Active Food Packaging - Muñoz-Shugulí, Cristina; Rodríguez-Mercado, Francisco; Mascayano, Carolina; Herrera, Andrea; Bruna, Julio E.; Guarda, Abel; Galotto, María J. (Frontiers in Nutrition, 2022)
Background: Allyl isothiocyanate is an excellent antimicrobial compound that has been applied in the development of active food packaging materials in the last years. However, the high volatility of this compound could prevent a lasting effect over time. In order to avoid this problem, cyclodextrin inclusion complexes have been proposed as an alternative, being beta-cyclodextrin (β-CD) as the main candidate. In addition, β-CD could act as a relative humidity-responsive nanoparticle. In this regard, the aim of this study was to develop inclusion complexes based on β-CD and AITC as relative humidity-responsive agents, which can be used in the design of active food packaging materials. Methods: Two different β-CD:AITC inclusion complexes (2:1 and 1:1 molar ratios) were obtained by the co-precipitation method. Entrapment efficiency was determined by gas chromatography, while inclusion complexes were characterized through thermal, structural, and physicochemical techniques. Antifungal capacity of inclusion complexes was determined in a headspace system. Furthermore, the AITC release from inclusion complexes to headspace at different percentages of relative humidity was evaluated by gas chromatography, and this behavior was related with molecular dynamic studies. Key Findings and Conclusions: The entrapment efficiency of inclusion complexes was over to 60%. Two coexisting structures were proposed for inclusion complexes through spectroscopic analyses and molecular dynamic simulation. The water sorption capacity of inclusion complexes depended on relative humidity, and they exhibited a strong fungicide activity against Botrytis cinerea. Furthermore, the AITC release to headspace occurred in three stages, which were related with changes in β-CD conformational structure by water sorption and the presence of the different coexisting structures. In addition, a strong influence of relative humidity on AITC release was evidenced. These findings demonstrate that β-CD:AITC inclusion complexes could be used as potential antifungal agents for the design of food packaging materials, whose activity would be able to respond to relative humidity changes.